The Determinants of a Successful Family Business Succession in Indonesia: A Multiple Case Study - Suresh Kumar; Qireina Prameswari (International Journal of Family Business Practices, 2018)
Family businesses play an important role in both developed and developing countries. They employ a majority of workforce establishing the newest jobs and generating a significant proportion of the gross domestic product. About 96% of the 165,000 companies established in Indonesia are family businesses. However, the survival rate of passing through the stage of second generations in family business is very low. This research has been conducted to analyse the determinants of successful family business successions. Qualitative research method was used to study four families. The conclusion from the study was that the determinants of successful family business succession are managing a complex relationship of successors and incumbent related factors, family context, business context, and having a structured agreement system.